On the role of intergranular nanocavities in long-term stress corrosion cracking of Alloy 690. (1st January 2022) - Shen, Zhao; Roberts, Edward; Saravanan, Naganand; Karamched, Phani; Terachi, Takumi; Yamada, Takuyo; Wu, Shengchuan; Tarleton, Edmund; Armstrong, David E.J.; Withers, Philip J.; Arioka, Koji; Lozano-Perez, Sergio
Abstract: The life extension of nuclear power plants beyond 60-years relies on the integrity of the steam generator tubes during the extended life. Alloy 690 steam generator tubes have been generally believed to be resistant to stress corrosion cracking (SCC) failures until the recent unexpected observation of intergranular cavities during long-term SCC testing. Here, a multi-technique characterisation approach has been used to study the behaviour of 30% cold worked samples exposed to long-term SCC testing at constant load. This has provided quantitative results on the effect of intergranular cavities and oxidation ahead of the crack tip. SCC mechanisms of creep cavity formation and associated oxidation through the cavity networks are discussed and the required stress to failure calculated, providing a quantitative measure of their weakening effect and a reliable way of assessing and predicting this important degradation problem. Graphical abstract: Image, graphical abstract